Interleukin-28 Polymorphism: Ethnic variations and the response to chronic hepatitis C treatment in Malaysia - Hoe, C.-H.; Suan, M.A.M.; Tang, T.-H.; Kiew, K.-K.; Hassan, M.R.A.; Chan, H.-K. (2018)
To date, information on the variations in IL-28 genotypes among different ethnic groups in Malaysia is still limited.After 24 weeks of treatment completion, blood samples were collected from all the patients to determine the SVR, and to identify their IL-28 genotypes using the methods and instruments as described in a similar study. The associations between IL28 genotypes and both ethnicity and SVR were confirmed using the Pearson's chi-square tests.In total, 72 patients were identified to have the CC genotype at the IL-28 polymorphic site. Interestingly, a higher proportion of the Chinese and Malay patients were found to have the CC genotype, as compared with the Indian patients, 62.5% of whom had the non-CC genotypes. The SVR rates for genotype-1 and genotype-3 HCV infections found in this study were, respectively, 53.3% and 68.2%. Additionally, despite the HCV genotypes, the patients with the CC genotype were confirmed to have a higher SVR rate compared with those with the nonCC genotypes. The information on variations in IL-28 genotypes across different ethnic groups could also be helpful in predicting responses to the interferon-based treatment among the CHC patients in Malaysia.